Research methods in occupational epidemiology - Checkoway, Harvey; Pearce, Neil.; Kriebel, David, 1955- (New York ; Oxford : Oxford University Press, 2004)
A clear and critical summary of research approaches to the epidemiological study of workplace hazards. The book describes the historical development of occupational epidemiology, methods for characterizing exposures, and techniques for designing and implementing epidemiologic studies in this area.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Occupational diseases -- Epidemiology